Spatial distribution analysis and application of engineering disturbance disasters in the Himalayan alpine valley - Song, Yewei; Guo, Jie; Ma, Fengshan; Liu, Jia; Li, Guang (Frontiers in Earth Science, 2023)
The Himalayan alpine canyon area is characterized by complex engineering geological conditions and abnormal internal and external dynamic geological processes. Severe slope disturbance disasters can be caused by engineering disturbances. In this study, field investigations and theoretical analyses were performed to determine the formation mechanism, spatial distribution law, and controlling factors of engineering disturbance disasters in the Himalayan alpine and canyon areas. A total of 396 engineering disturbance disasters were identified within the scope of the 2800-km survey line. A geographic information system and mathematical statistical analysis were used to analyze the correlation between engineering disturbance disasters and factors such as the slope, slope aspect, elevation, peak ground acceleration, distance from fault, distance from river, rainfall, lithological changes, and historical earthquake effects. The statistical analysis indicates a good exponential distribution between the engineering disturbance disaster concentration and the slope and distance from the river. The slope and distance from the river are the two most important factors in determining the spatial distribution of engineering disturbance disasters; the other factors also influence the distribution to some extent. These factors affect the quality of the slope rock and soil mass, affecting slope stability. The main form of engineering disturbance in the study area is slope cutting. The direct result (increase in slope) and secondary result (decrease in rock mass quality caused by unloading rebound) of slope cutting are the most important factors inducing engineering disturbance disasters. Based on previous research results, factors in engineering disturbance disasters in alpine and canyon areas were evaluated, and the distribution of disturbance disasters along the China–Nepal Railway was predicted. The study area was divided into extremely high- (13.6%), high- (30.4%), medium- (34.1%), and low-susceptibility (22.0%) areas. The research results can provide a theoretical basis for prevention and treatment of engineering disturbance disasters in Himalayan alpine valley areas.